MENINGKATKAN KREATIVITAS ANAK SEBAGAI OPTIMALISASI PERKEMBANGAN KOMPREHENSIF ANAK USIA DINI - Asiyah, Asiyah (Al Fitrah: Journal Of Early Childhood Islamic Education, 2018)
Education is the process of changing one's attitude or behavior groups of people to mature humans through teaching and training efforts. Since early humans have needed education in the process of its development into adulthood. The development of children in the first years is very important and will determine the quality in the future. Children are individuals who are different, unique, and have their own characteristics in accordance with the stages of his age. Therefore, early childhood development efforts should be done through learning and play.Growth and physical development have an important role in the lives of children. Growth and physical development is one of the major developmental tasks in the life of a child. Growth and physical development will affect the development and growth of children in other developmental dimensions. Parents and teachers really need to understand the growth and physical development of children, and instill healthy habits through physical activity of children from an early age.To help the physical development of children, teachers and parents need to provide guidance to them in order to have the awareness of sensory abilities, and also have a positive attitude towards him. Parents and teachers also need to understand the signs of developmental delays in children, parents and teachers need to be cautious in view of delays in child development and should consult with your doctor to make sure and give the child needed help, so that children can grow physically and develop optimally.  Keywords: physical development, early childhood